Modulation of Cross-Language Activation During Bilingual Auditory Word Recognition: Effects of Language Experience but Not Competing Background Noise - Fricke, Melinda (Frontiers in Psychology, 2022)
Previous research has shown that as the level of background noise increases, auditory word recognition performance drops off more rapidly for bilinguals than monolinguals. This disproportionate bilingual deficit has often been attributed to a presumed increase in cross-language activation in noise, although no studies have specifically tested for such an increase. We propose two distinct mechanisms by which background noise could cause an increase in cross-language activation: a phonetically-based account and an executive function-based account. We explore the evidence for the phonetically-based account by comparing cognate facilitation effects for three groups of native English listeners (monolinguals, late (L2) learners of Spanish, and heritage Spanish speakers) and four noise conditions (no noise, speech-shaped noise, English two-talker babble, and Spanish two-talker babble) during an auditory lexical decision task in English. By examining word recognition in the dominant language, the role of language control mechanisms is minimized, and by examining three different types of competing noise, the role of energetic vs. informational masking can be assessed. Contrary to predictions, we find no evidence that background noise modulates cross-language activation; cognate facilitation is constant across the four noise conditions. Instead, several indices of word recognition performance are found to correlate with aspects of linguistic experience: (1) The magnitude of the cognate facilitation effect is correlated with heritage listeners' self-ratings of Spanish proficiency; (2) Overall noise deficits are larger for heritage listeners with lower English vocabulary scores; (3) Heritage listeners' Spanish self-ratings predict their magnitude of informational masking; (4) For all bilinguals, the degree of masking incurred in both English and Spanish two-talker babble is correlated with self-reported daily exposure to Spanish; and (5) The degree of masking incurred by Spanish babble is correlated with Spanish vocabulary knowledge. The results enrich our understanding of auditory word recognition in heritage speakers in particular, and provide evidence that informational masking is most subject to modulation due to variation in linguistic experience. It remains to be seen whether cross-language activation is modulated by noise when the target language is the less dominant one.